METHODS OF DEVELOPING THE SPEECH OF PRIMARY STUDENTS BASED ON AN INTEGRATIVE APPROACH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article describes in detail the general features of the integrative approach to speech development in primary school students. Didactic games, oratory, riddles that develop speech.